Attitude of Teachers towardsDigital Class Room and its variation with other Variables - SHARMA, DRSUGAN; Sharma, Rajesh Kumar (Innovare Journal of Education, 2016)
The present paper is an attempt to study the attitude of teachers based on their Age, Gender, Experience and Faculty/Streamin the middle school with the help of Digital Class Room. It is a computer based teaching aid which has pre stored detailed syllabus of each topic for a subject for a particular class group thatis to be taught.